Spatial partial coherence in Young's interferograms - Castañeda, Román (1998)
Young's interferograms with high visibility reveals a high degree of spatial coherence of first order. But, spatially partial coherence of second order can be observed when it interferes itself through a compensated Michelson's interferometer attached at the exit of the Young's slit pair. We show that the patterns at the exit of the Michelson's interferometer are Young's interferograms with modulation fringes, which allow an estimation of the degree of the high order spatial coherence.